2003
DOI: 10.1590/s1517-86922003000600004
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do ácido láctico intramuscular através da espectroscopia Raman: novas perspectivas em medicina do esporte

Abstract: O uso da espectroscopia Raman no infravermelho pode vir a constituir uma nova técnica para avaliação física, permitindo medidas da concentração de ácido láctico em sangue e em músculo esquelético, por um método não invasivo. A espectroscopia Raman é uma técnica que oferece grande riqueza de detalhes provida pela vibração de moléculas em diferentes níveis de energia. Em estudos prévios, foram obtidos espectros Raman de ácido láctico em plasma humano e em sangue de rato, onde os picos característicos foram obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Raman spectroscopy is an optical tool that allows less-invasive and nondestructive analysis of tissues, allowing one to obtain precise information on the biochemical composition of the tissue. 42 A previous report 43 demonstrated the presence of lactic acid in tibiae muscle in rats, and another used Raman spectroscopy to investigate the effects of LLLT on the healing of dental implants of rabbits by monitoring the level of calcium phosphate after surgery. 44 Another study reported the use of Raman spectroscopy to monitoring protein structure in muscle.…”
Section: Introductionmentioning
confidence: 99%
“…Raman spectroscopy is an optical tool that allows less-invasive and nondestructive analysis of tissues, allowing one to obtain precise information on the biochemical composition of the tissue. 42 A previous report 43 demonstrated the presence of lactic acid in tibiae muscle in rats, and another used Raman spectroscopy to investigate the effects of LLLT on the healing of dental implants of rabbits by monitoring the level of calcium phosphate after surgery. 44 Another study reported the use of Raman spectroscopy to monitoring protein structure in muscle.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the study of techniques based on Raman spectroscopy for deep non-invasive probing of diffusely scattering media such as living tissue and powders, is an emerging area in order to promote several applications, such as quality control of pharmaceutical products [25]. Moreover, new approaches have used Raman spectroscopy in sportive medicine in order to evaluate the production of lactic acid inside of several muscles with auspicious results [26].…”
Section: Introductionmentioning
confidence: 99%